El impresor Antonio Espinosa de los Monteros en Madrid: avance para su estudio. - Reyes Gómez, Fermín de los (Revista General de Información y Documentación, 2004)
Antonio Espinosa de los Monteros is known as an engraver of letters for the press and as a printer in Segovia in the years 1777 to 1812, but hardly at all as a printer in Madrid (1787-1812). This article gives an advance of the contents of a study which is under way dealing with both his biography and the setting up of the press in Madrid where he was a notable printer. The final part includes a provisional bibliographical repertory with the production from his presses in Madrid.